Training or Retiring? How Labor Markets Adjust to Trade and Technology Shocks - Alexander Bertermann; Wolfgang Dauth; Jens Suedekum; Ludger Woessmann (Institute of Labor Economics (IZA), 2025)
How do firms and workers adjust to trade and technology shocks? We analyze two mechanisms that have received little attention: training that upgrades skills and early retirement that shifts adjustment costs to public pension systems. We combine novel data on training participation and early retirement in German local labor markets with established measures of exposure to trade competition and robot adoption. Results indicate that negative trade shocks reduce training—particularly in manufacturing—while robot exposure increases training—particularly in indirectly affected services. Both shocks raise early retirement among manufacturing workers. Structural change thus induces both productivity-enhancing and productivity-reducing responses, challenging simple narratives of labor market adaptation and highlighting the scope for policy to promote adjustment mechanisms conducive to aggregate productivity.
Keywords: J24; J26; O33; F16; R11; 330; training; retirement; trade; technological change; automation; robots; firms; workers; labor market